Biogeochemical Cycling of Colloidal Trace Metals in the Arctic Cryosphere. Issue 8 (5th August 2021) - Jensen, Laramie T.; Lanning, Nathan T.; Marsay, Chris M.; Buck, Clifton S.; Aguilar‐Islas, Ana M.; Rember, Robert; Landing, William M.; Sherrell, Robert M.; Fitzsimmons, Jessica N.
Abstract: The surface waters of the Arctic Ocean include an important inventory of freshwater from rivers, sea ice melt, and glacial meltwaters. While some freshwaters are mixed directly into the surface ocean, cryospheric reservoirs, such as snow, sea ice, and melt ponds act as incubators for trace metals, as well as potential sources to the surface ocean upon melting. The availability and reactivity of these metals depends on their speciation, which may vary across each pool or undergo transformation upon mixing. We present here baseline measurements of colloidal (∼0.003–0.200 μm) iron (Fe), zinc (Zn), nickel (Ni), copper (Cu), cadmium (Cd), and manganese (Mn) in snow, sea ice, melt ponds, and the underlying seawater. We consider both the total concentration of colloidal metals ([cMe]) in each cryospheric reservoir and the contribution of cMe to the overall dissolved metal phase (%cMe). Notably, snow contained higher (cMe) as well as higher %cMe relative to seawater for metals such as Fe and Zn across most stations. Stations close to the North Pole had relatively high aerosol deposition, imparting high (cFe) and (cZn), as well as high %cFe, %cZn, %cMn, and %cCd (>80%). In contrast, surface seawater concentrations of Cd, Cu, Mn, and Ni were dominated by the soluble phase (<0.003 μm), suggesting little impact of cMe from the melting cryosphere, or rapid aggregation/disaggregation dynamics within surface waters leading to the loss of cMe. This has important implications for how trace metal biogeochemistry speciation and thus fluxes may change in a future ice‐free Arctic Ocean. Plain Language Summary: The Arctic Ocean is particularly vulnerable to climate change that results in increased freshwater inputs, such as river discharge and sea ice melt. This may also result in an increase or decrease in nutrient supply to the microorganisms living in the surface ocean who have metabolic requirements for survival. In fact, microorganisms need "trace" metals, found in very low abundances, that can be supplied by rivers and sea ice. However, the physical size of these metals may change how available they are to microorganisms. Here, we examine a size spectrum (∼0.003–0.200 μm) of important trace metals within snow, sea ice, melt ponds that form on sea ice, and the underlying seawater. These frozen reservoirs may serve as temporary "holding areas" for small trace metal particles to aggregate or dissolve, thus changing their availability or reactivity to microorganisms. Our goal was to assess what percentage of the overall sample is "small" (soluble <0.003 µm) versus "intermediate" (colloidal ∼0.003–0.200 µm) for each metal and how that changes between snow, sea ice, melt ponds, and seawater. As these frozen reservoirs decline in the Arctic it is important to understand their metal and nutrient supply to the surface ocean to predict how this may change in the future. Key Points: Melt ponds act as a incubator for biotic and abiotic aggregation and disaggregation of colloidal trace metals There are higher proportions of colloids for Fe, Zn, Ni, Cd, and Mn in Arctic sea ice, snow, and melt ponds, compared to surface seawater There is colloidal Fe and Zn loss moving from snow to melt ponds and sea ice to underlying seawater during "incubation" in the cryosphere